"More Realism, Critically"—A Reply to James K. A. Smith’s "The (Re)Turnto the Person in Contemporary Theory" - Smith, Christian (Christian scholar's review, 2011)
I am grateful for James K. A. Smith’s (hereafter JS) very thoughtful review (see Christian Scholar’s Review 40.1 [Fall 2010]: 77-92) of my book, What is a Person? (here-after WiaP?). Much of his exposition gets the book and my larger intellectual project right, which I greatly appreciate. But some of his critical arguments I think miss the mark. Here I address some issues that come up in his review that strike me as debatable and relevant to CSR readers.